Peran Bidan dalam Deteksi Dini Depresi Postpartum pada Ibu Nifas - Nurul Huda Jamil; Sri Dewi Haryati; Hazen Aziz (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Postpartum depression (PPD) is a common and serious mental health disorder for mothers after givingbirth, which is a public mental health problem because it not only has a direct impact on the baby, but also on the family. The most common symptoms of PPD are overwhelming sadness, feelings of hopelessness and helplessness, moodiness, an inability to experience joy with the baby, serve anxienty, loss of appetite, poor concentration and memory, sleep disturbances, prolonged fatigue, and suicidal ideation (American Psychological Association, 2013). The design used in this study was quantitative by measuring the prevalence of postpartum depression in postpartum mothers using the EPDS form. The research was conducted at Gandapura Community Health Center, this location wa used as the research site because it had not been exposed at all regarding the use of the EPDS form as part of the initial assessment of midwifery services. A population is all elements that meet certain criteria for inclusion in a study. The population in this study was all postpartum mothers who gave birth in the obstetrics ward. The sample criteria in this study are divided into two, namely inclusion criteria and exclusion criteria. Conclusion: Postpartum guidance provided to mothers influences the risk of postpartum depression. Postpartum women who receive assistance are less likely to experience postpartum depression, and mothe who do not receive assistance are depression.